Durability of latent heat storage systems - Sylva Bantová; Milan Ostrý; Karel Struhala (Acta Polytechnica CTU Proceedings, 2022)
Latent heat storage represents technology with significantly higher energy storage density. The thermal energy storage capacity of building structures and storage units integrated into building services contribute to the energy flexibility of buildings. This paper presents results from laboratory experiments focused on the compatibility of heat storage media represented by phase change materials (PCMs) with materials of container. Material compatibility of selected PCMs with the plastics and metals were tested by a long-term experiment. Two organic-based and two inorganic-based phase change materials were selected for tests of compatibility with selected metals (aluminium, copper and brass) and plastics (PP-H, PE-HD, and PVC-U). Plastic-PCM compatibility was determined by gravimetric method. For evaluation of metal-PCM compatibility, calculation of corrosion rate was applied. The less mass changes and lower penetration of PCMs to the matrix was observed for inorganic-based PCMs compared to organic-based PCMs. In case of compatibility between metals and PCMs, the highest values of corrosion rate were calculated for copper immersed in inorganic-based PCMs Rubitherm SP25.